1999
DOI: 10.1093/brain/122.4.657
|View full text |Cite
|
Sign up to set email alerts
|

Humour appreciation: a role of the right frontal lobe

Abstract: Humour occupies a special place in human social interactions. The brain regions and the potential psychological processes underlying humour appreciation were investigated by testing patients who had focal damage in various areas of the brain. A specific brain region, the right frontal lobe, most disrupted the ability to appreciate humour. The individuals with damage in this brain region also reacted less, with diminished physical or emotional responses (laughter, smiling). Performance on the humour appreciatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
194
1
14

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(223 citation statements)
references
References 33 publications
14
194
1
14
Order By: Relevance
“…Reasoning with neutral content resulted in greater activation in L/DLPFC cortex (over and above the neutral baseline) than reasoning with emotionally salient content (over and above the emotionally salient baseline). Consistent with this role, the L/DLPFC has been implicated in a series of "executive" cognitive tasks including the WCST (Drewe, 1974;Stuss et al, 2000), Tower of London (Fincham et al, 2002;Rowe et al, 2001;Shallice, 1988), the Stroop task (Perret, 1974;Weekes and Zaidel, 1996), design fluency (Jones-Gotman and Milner, 1977), cognitive estimation (Smith and Milner, 1984), planning and design (Goel and Grafman, 2000;, and tasks (like humor appreciation) requiring the "breaking of mental sets" (Goel and Dolan, 2001a;Shammi and Stuss, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Reasoning with neutral content resulted in greater activation in L/DLPFC cortex (over and above the neutral baseline) than reasoning with emotionally salient content (over and above the emotionally salient baseline). Consistent with this role, the L/DLPFC has been implicated in a series of "executive" cognitive tasks including the WCST (Drewe, 1974;Stuss et al, 2000), Tower of London (Fincham et al, 2002;Rowe et al, 2001;Shallice, 1988), the Stroop task (Perret, 1974;Weekes and Zaidel, 1996), design fluency (Jones-Gotman and Milner, 1977), cognitive estimation (Smith and Milner, 1984), planning and design (Goel and Grafman, 2000;, and tasks (like humor appreciation) requiring the "breaking of mental sets" (Goel and Dolan, 2001a;Shammi and Stuss, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…They compared semantic and phonological jokes that were rated as funny with jokes that were not, and reported activation in medial ventral PFC and bilateral cerebellum, which co-varied significantly with funniness ratings. In addition, the findings of the lesion study by Shammi and Stuss (1999) suggested a contribution of the PFC to humor processing. The observed humor processing deficits in the present investigation may thus be linked to PFC dysfunction in major depression, as shown by recent studies (Veiel, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, investigations have focused on the contribution of the prefrontal cortex to humor processing (Wild et al, 2003). Shammi and Stuss (1999) reported that patients with prefrontal lesions rated the jokes to be less funny and selected more nonsensical endings (i.e., those involving incongruity detection but no resolution). Heath and Blonder (2005) reported that patients with damage to the right hemisphere involving the frontal lobes responded less strongly to humor compared to patients with damage to the right hemisphere without frontal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the frontal lobes help instigate laughter, and the right frontal lobes may be especially important for the appreciation of humor [85]. A remarkable recent discovery is the induction of hearty laughter, accompanied by true mirth, during presurgical stimulation of a frontal cortical area (i.e., the supplementary motor cortex), that has long been recognized as important in the initiation of movement.…”
Section: The Neural Substrates Of Laughter In Humansmentioning
confidence: 99%